Herpes simplex virus detection and genomes from under-sampled, remote populations - Christopher D. Bowen; Alexandre Blake; Daniel W. Renner; Mary Ashley Hazel; John Jakurama; Justy Matundu; Moriah L. Szpara; Nita Bharti (PLoS ONE, 2026)
Herpes simplex virus (HSV) is an endemic pathogen, infecting over half of all adults world-wide. HSV infection can cause a wide spectrum of disease outcomes, ranging from asymptomatic infection or mild lesions to rare cases of infectious keratitis, encephalitis, and death. HSV genome sequences differ between individuals and within individuals. To date, the vast majority of publicly available HSV genomic data has come from Europe and North America. Populations in South America, Africa, and Asia are under-sampled, as are non-industrial (e.g., agricultural, pastoral) populations, for which the natural environment plays a large role in health and disease dynamics. We used Whatman FTA card stabilization of DNA to develop a procedure for capturing oral and genital swabs from a geographically isolated pastoralist population in a desert region of northern Namibia. This is the first study to document HSV genome sequences from this type of remote setting and these are the first HSV genomes from Namibia. The resulting HSV sequences, collected in 2015 and 2016 from remote settlements in Namibia, fit within the scope of viral genetic diversity previously defined by African strains. The methodological approaches developed in this study can be expanded to broaden viral detection, improve diagnostics, and raise public health awareness about the burden of pathogens in under-served populations.